Establishment of standardised SLA/LP immunoassays: specificity for autoimmune hepatitis, worldwide occurrence, and clinical characteristics. Issue 2 (1st August 2002) - Baeres, M; Herkel, J; Czaja, A J; Wies, I; Kanzler, S; Cancado, E L R; Porta, G; Nishioka, M; Simon, T; Daehnrich, C; Schlumberger, W; Galle, P R; et al.
Abstract : Background: Antibodies to soluble liver antigen/liver pancreas (SLA/LP) are specific markers of autoimmune hepatitis. Their target antigen has recently been cloned. Aims: To establish standardised immunoassays using the recombinant antigen, and to assess the frequency and significance of seropositivity in patients from different countries. Methods: An enzyme linked immunoassay was developed using purified recombinant antigen and validated by testing sera from 200 healthy blood donors and 1026 patients with various liver and non-liver diseases. The assay was then applied to 454 sera from 419 patients with autoimmune hepatitis from different countries. All sera were also tested by inhibition immunoassay and western blot. Results: Antibodies were reliably detected by the recombinant immunoassay and occurred exclusively in patients with autoimmune liver disease. Twenty three of 149 patients from the USA (15%), 23/132 from Brazil (17%), 21/108 from Germany (19%), and 2/30 from Japan (7%) were seropositive. Clinical features at presentation were similar between seropositive and seronegative patients. However, relapse after corticosteroid withdrawal or during maintenance therapy occurred more commonly in seropositive patients. Conclusions: Antibodies to SLA/LP can be reliably detected by these standardised immunoassays based on recombinant antigen. Antibodies to SLA/LP occur with similar frequencies in different geographical regions, races, and age groups, and are of exquisite diagnostic specificity. Whether SLA/LP positive patients represent a clinically distinct subgroup remains to be determined; relapse during treatment reduction appeared to be more common in the SLA/LP group.